The Movement to Maintain Food Security Through Technological Advancements and Local Diversification: Ministry of Agriculture Republic of Indonesia - Herlina, Nia; Wahyuni, Herpita; Winahyu, Fauziyya Puji; Anwar, Khairul; Heliana (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2024)
This study aims to determine the food security movement using a qualitative descriptive research method assisted by NVivo 12 Plus software from the Twitter account data source of the Ministry of Agriculture Republic of Indonesia, supported by previous research. Data coding was obtained from Twitter, social media, and news data, which supported the findings using a crosstab query feature. The analysis found that the government's strategy for maintaining food security was to increase production capacity, diversify local food, strengthen food reserves and logistics systems, and develop modern agriculture. They increased food production by intensifying 85,456 hectares of swamp land and maximizing 85,456 hectares of land. Diversifying local food by massively utilizing local food as an alternative food supply and strengthening food reserves and logistics systems by supporting food reserves that can be used to help other areas affected by disasters as a form of social care, and developing modern agriculture with Smart Farming Developing technology-based clever farming methods, including Agri Drone Sprayer liquid, Surveillance Drones (drones for land mapping), Soil and Weather Sensors, as well as the development of food safety applied to households. Scale with vertical hydroponic growing system training.